2021
DOI: 10.3389/fimmu.2021.639650
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation Eliminates Inflammation in the Hippocampus in Experimental Autoimmune Encephalomyelitis, but Does Not Ameliorate Anxiety-Like Behavior

Abstract: Multiple sclerosis (MS) is an autoimmune disease targeting the central nervous system, characterized by an unpredictable disease course and a wide range of symptoms. Emotional and cognitive deficits are now recognized as primary disease manifestations and not simply the consequence of living with a chronic condition, raising questions regarding the efficacy of current therapeutics for these specific symptoms. Mechanisms underlying psychiatric sequelae in MS are believed to be similar to those underlying pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…There are some conflicting data about fingolimod's ability to reduce anxiety-like behaviors in EAE models of MS. While It was previously shown that fingolimod reduces anxiety-like behavior (Bonfiglio et al, 2017), a new study fails to show anxiety-like symptoms in EAE mice models of MS (Kocovski et al, 2021). Mounting evidence suggests that fingolimod also has neuroprotective activity (Slowik et al, 2015;Sternberg et al, 2018;Yang et al, 2021) and acts as a myelin regeneration booster by affecting neural precursor cells and oligodendrocytes lineage (Coelho et al, 2007;Miron et al, 2010;Heinen et al, 2015;Qin et al, 2017).…”
Section: Multiple Sclerosismentioning
confidence: 98%
“…There are some conflicting data about fingolimod's ability to reduce anxiety-like behaviors in EAE models of MS. While It was previously shown that fingolimod reduces anxiety-like behavior (Bonfiglio et al, 2017), a new study fails to show anxiety-like symptoms in EAE mice models of MS (Kocovski et al, 2021). Mounting evidence suggests that fingolimod also has neuroprotective activity (Slowik et al, 2015;Sternberg et al, 2018;Yang et al, 2021) and acts as a myelin regeneration booster by affecting neural precursor cells and oligodendrocytes lineage (Coelho et al, 2007;Miron et al, 2010;Heinen et al, 2015;Qin et al, 2017).…”
Section: Multiple Sclerosismentioning
confidence: 98%
“…In even more severe cases, there is complete hind and partial front limb paralysis, a severe condition where euthanasia is strongly recommended. Although several other behavioral domains are affected in the diverse EAE models, including the sensory domain [ 14 , 15 , 16 ] and cognition [ 17 , 18 , 19 ], or there is anxiety-like behavior [ 20 , 21 ], it is the motor behavioral deficit that serves as the primary outcome measurement in most of the EAE studies.…”
Section: Preclinical Ms Modelsmentioning
confidence: 99%
“…[126][127][128][129] Coupled with technological advances already mentioned, behavioral studies provide powerful insight into brain networks. In this context, we and others have identified anxiety-like behavior prior to the earliest detectable accumulation of autoreactive T cells in EAE 90,91 in evaluation of depressive-like behavioral syndrome due to MS.…”
Section: Cognitive Functionmentioning
confidence: 89%
“…Testing should be performed with the collaboration of behavioral experts because of the complexity of data analysis, especially when dealing with NHP. The timing of the tests is also of critical importance 90,91 and should not rely on clinical scoring of ambulatory difficulties which are a reflection of spinal cord rather than cerebellar damage. They must be based on prior establishment of the spatio-temporal pattern of disease development specifically in the cerebellum. 6.…”
Section: A Role For Experimental Autoimmune Encephalomyelitis In Unde...mentioning
confidence: 99%